2000
DOI: 10.1006/jfls.1999.0275
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Boundary Element Method Applied to Laminar Vortex-Shedding From Arrays of Cylinders in Various Arrangements

Abstract: A cell boundary element method is used to solve the two-dimensional incompressible Navier} Stokes equation for vortex-shedding #ows around arrays of cylinders. The method is a hybrid scheme using a boundary element method in each #uid cell discretization with a "nite element procedure to solve for the global #uid problem. Computations are presented of two-dimensional #ow characteristics and interactive forces associated with #ows around four equispaced cylinders of equal diameter, and two cylinders, one with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 30 publications
(33 reference statements)
7
28
1
Order By: Relevance
“…is 0.194. In Table I, present results are compared with experimental results [9,10] and other calculations [1,11,12]. The present results are in good agreement with experimental and other numerical results.…”
Section: Flow Over a Circular Cylinder At A Reynolds Number Of 200supporting
confidence: 94%
“…is 0.194. In Table I, present results are compared with experimental results [9,10] and other calculations [1,11,12]. The present results are in good agreement with experimental and other numerical results.…”
Section: Flow Over a Circular Cylinder At A Reynolds Number Of 200supporting
confidence: 94%
“…If required, these records may be extended but the lengths presented illustrate typical patterns. Farrant et al (2000) previously showed that the wake developed behind side-by-side cylinders at different spacing simulates closely the experimental evidence observed by Williamson (1985).…”
Section: Numerical Predictions 31 Time Simulationssupporting
confidence: 81%
“…Recent efforts, employing different types of numerical simulation, include those of Mittal et al (1997) and Farrant et al (2000), also at relatively low values of Reynolds number.…”
Section: Introductionmentioning
confidence: 99%